2008
DOI: 10.1176/appi.ajp.2008.08010077
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance in Bipolar Disorder: Therapeutic Implications

Abstract: In this review, the authors detail our current understanding of the crucial role that sleep and its disturbances play in bipolar disorder. Multiple lines of evidence suggest that impaired sleep can induce and predict manic episodes. Similarly, treatment of sleep disturbance may serve as both a target of treatment and a measure of response in mania. The depressive phase of bipolar illness is marked by sleep disturbance that may be amenable to somatic therapies that target sleep and circadian rhythms. Residual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(155 citation statements)
references
References 136 publications
9
143
0
3
Order By: Relevance
“…One exception to this involves pregnant women with a bipolar disorder or past or current psychosis, in whom sleep plays a crucial role in the prevention of postpartum psychosis. 36 …”
Section: Discussionmentioning
confidence: 99%
“…One exception to this involves pregnant women with a bipolar disorder or past or current psychosis, in whom sleep plays a crucial role in the prevention of postpartum psychosis. 36 …”
Section: Discussionmentioning
confidence: 99%
“…They are also more likely to report sleep disturbances, which have a serious impact on mood stability. 28 This association between comorbid anxiety disorders and mood stability points to the critical importance of taking anxiety into account as a key feature when treating these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, significant sleep-BPD associations were also found in community (Oltmanns et al, 2014;Selby, 2013) and prison (Harty et al, 2010) Fifth, some studies concentrated on the effects of comorbid or past history of depression (Akiskal, Yerevanian, Davis, King, & Lemmi, 1985), or just controlled for depression symptoms (Oltmanns et al, 2014), rather than a full range of psychiatric disorders. Bipolar disorder and post-traumatic stress disorder, for example, have been associated with both BPD (Zimmerman & Mattia, 1999) and sleep disturbance (Kobayashi, Boarts, & Delahanty, 2007;Plante & Winkelman, 2008). Nevertheless, the majority of studies did exclude participants with other psychiatric disorders (e.g., psychotic disorder, bipolar disorder, substance abuse, PTSD) or controlled for other psychiatric symptoms, e.g., substance abuse, PTSD (Harty et al, 2010;Selby et al, 2013), adding support to the independence of observed associations between BPD and sleep disturbance.…”
Section: Strengths and Limitationsmentioning
confidence: 99%